Verbal Disagreeing Strategies in Detective Conan Movie Series (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
This study is meant to investigate the ways of male and female criminals express types of verbal disagreeing strategies in Detective Conan movie series. To collect the data, 30 criminals (15 males, 15 females) were selected among hundreds of criminals appeared in the movie. The criminals were expected to disagree with 6 chosen interlocutors when they do debate over the accusation pointed to the criminals. The types of disagreeing strategies which help the researcher to analyze the disagreeing strategies in criminals are based on Muntigl and Turnbull taxonomy (in Behnam & Niroomand, 2011:208). Qualitative content analysis is chosen to examine the criminals' disagreeing strategies. The results show that male criminals performed more disagreeing strategies by applying 56 disagreements, and female criminals applied 48 disagreements. From those disagreements, it is found new types of disagreeing strategies in addition to the types from the taxonomy of Muntigl and Turnbull (in Behnam & Niroomand, 2011:208)